Ketentuan Syarat Adil Bagi Saksi Nikah Dalam Pandangan Kepala Kantor Urusan Agama Se-Kota Palangka Raya - Mahmud Mahmud (International Journal Labs, 2022)
Marriage is one of the sexy topics to be discussed, both in the midst of society and in the academic community, because marriage has the meaning of worship, for that it is necessary to complete the conditions and pillars of marriage so that the goal can be achieved. One of the 5 (five) pillars of marriage is fair. Imam Syafii, Imam Abu Hanifah have different opinions regarding the determination and criteria for fair witnesses in marriage. Imam Syafii said a marriage is not valid if it is not attended by two fair witnesses while Imam Abu Hanifah said a witness does not have to be fair, including also regarding the legal status of marriage if the witness is unfair. Referring to this background, the focus of this research is to discuss the views of the heads of KUA throughout Palangka Raya on the provisions of fair conditions for marriage witnesses.This study uses a qualitative descriptive approach included in the cluster of empirical research. The data collection techniques used are observation, interviews, and documentation which are semi-structured as well as online data searches (library research). Data analysis techniques in this study are: 1. Data collection; 2. Data reduction; 3. Presentation of data and drawing conclusions.The general results of the research focused on the views of the heads of KUA throughout Palangka Raya on the provisions of fair conditions for marriage witnesses, where the witness determination procedure carried out so far has 4 (four) stages namely, taking marriage requirements, returning physical evidence, counseling candidates the bride and groom and shortly before the wedding ceremony. fair conditions. Honest, trustworthy, understand religious law, role model and impartial. Marital status if the marriage witness is considered unfair, then the witness does not need to be replaced with another person because in addition to the appointed witness, all the invitees who were present at the time of the marriage contract event were also witnesses. involved in the procession should read the istigfar and the shahada.